The human paradox : rediscovering the nature of the human : an essay on the metaphysics of the virtues - Heintzman, Ralph (University of Toronto Press, 2022)
"What is a human being? What does it mean to be human? How can you lead your life in ways that best fulfill your own nature? In The Human Paradox, Ralph Heintzman explores these vital questions and offers an exciting new vision of the nature of the human. The Human Paradox aims to counter or correct several contemporary assumptions about the nature of the human, especially the tendency of Western culture, since the seventeenth century, to identify the human with rationality and the rational mind. Using the lens of the virtues, The Human Paradox shows how rediscovering the nature of the human can help not just to understand one's own paradoxical nature but to act in ways that are more consistent with its full reality. Offering accessible insight from both traditional and contemporary thought, The Human Paradox shows how a fuller, richer vision of the human can help address urgent contemporary problems, including the challenges of cultural and religious diversity, human migration and human rights, the role of the market, artificial intelligence (AI), the future of democracy, and global climate change. This fresh perspective on the Western past will guide readers into what it means to be human and open new possibilities for the future."--